Strategic Initiatives for Digital Transformation in Inclusive Procurement Ecosystems of UKPBJ Kemenkeu - Gunawan, Edy; Mutaqin, Muhammad Iqbal (PT Agung Media Publisher, 2024)
Digital transformation is essential for modernizing public procurement systems, particularly within the Procurement Unit of the Ministry of Finance of the Republic of Indonesia (UKPBJ Kemenkeu). This paper explores the strategic design and implementation of such transformation, emphasizing its role in fostering efficiency, transparency, and sustainability in procurement processes. A qualitative approach was employed, analyzing the integration of digital tools and strategies across four foundational pillars: changes in work patterns and governance, business process simplification, human resource empowerment, and a data-driven approach. Data were collected through organizational records, interviews, and case studies of the implemented initiatives. The transformation strategy yielded five interrelated initiatives that culminated in eleven synergistic innovations. These initiatives streamlined procurement workflows, enhanced inter-agency collaboration, and improved decision-making through real-time data analysis. The findings highlight the importance of aligning digital transformation with organizational goals and stakeholder needs. Key success factors included leadership commitment, cross-functional collaboration, and adaptive capacity-building efforts. The digital transformation efforts at UKPBJ Kemenkeu have significantly improved the effectiveness and efficiency of procurement processes. These innovations provide sustainable benefits for the organization and its stakeholders, positioning the unit as a model for inclusive and accountable public procurement.